(untitled) (Teacher’s World: Journal of Education and Research, 2023)
This article explores the role of Bangabandhu Sheikh Mujibur Rahman as a first woman-friendly statesman in Bangladesh. His role has not been investigated in the light of gendered discourse who broke the culture of silence by acknowledging the roles of Bangali women, their heroic and courageous deeds, dedication and huge contribution to Bangali nationalist discourse and political trajectory. Mujibian notion of gender and his perception of women’s empowerment has equally not been discovered in academic discourse and political scholarship. He has been regarded as the first woman-friendly statesman in this article for (1) providing critical insight into the traditional narrative of the socio-political history of Bangladesh (2) challenging the stereotypical outlook of the patriarchal society towards Bangali women with the introduction of a new insight and (3) moving for the advancement of the society with women empowerment in a very pragmatic manner. Vol. 48 (University of Dhaka Centennial Special Issue), June 2022 p.27-34